Karyn Lai, Learning from Chinese Philosophies: Ethics of Independent and Contextualised Self, Aldershot, UK: Ashgate, 2006, 218 pp., ISBN: 0754633829, hb - Tan, Sor-hoon (Sophia, 2007)
Learning from Chinese Philosophies explores early Confucianism and Daoism in order to engage today’s problems. By bringing into thoughtful play Confucian ideas of self and society and Daoist understanding of situated self, the author uses the debate between the two philosophies to argue for her understanding of Confucian moral thinking and Daoist metaethics. According to Lai, Daoist metaethics question dichotomous frameworks and discuss the unity of opposites enabling dynamic interplay of nonantagonistic polarities. Lai not only rejects comparisons of Confucianism to consequentialist and deontological moral theories, but also the view that Confucian ethics is a form of virtue ethics. Instead, she argues that the Analects is a manual for moral decision making that requires skills “to unravel and analyse the complex features of particular situations and to pick out those which are morally relevant.” Together, Confucianism and Daoism offer views of interdependent relationality that help to reconceptualize contemporary problems and criticize existing thinking and practices. Lai applies what she has learned from these two Chinese philosophies in a critique of feminist care ethics. Despite a few flaws, this is a clearly written work with stimulating interesting ideas and it lives up to the promise of demonstrating the continued relevance of Chinese philosophies.